2021
DOI: 10.1038/s41467-021-21328-8
|View full text |Cite
|
Sign up to set email alerts
|

Active-site loop variations adjust activity and selectivity of the cumene dioxygenase

Abstract: Active-site loops play essential roles in various catalytically important enzyme properties like activity, selectivity, and substrate scope. However, their high flexibility and diversity makes them challenging to incorporate into rational enzyme engineering strategies. Here, we report the engineering of hot-spots in loops of the cumene dioxygenase from Pseudomonas fluorescens IP01 with high impact on activity, regio- and enantioselectivity. Libraries based on alanine scan, sequence alignments, and deletions al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 72 publications
4
48
0
Order By: Relevance
“…This observation demonstrated that the formation of new tunnels and widening of existing ones can modulate the catalytic activity of enzymes. It also resembled the findings reported for prior studies [ 46 , 47 ].
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…This observation demonstrated that the formation of new tunnels and widening of existing ones can modulate the catalytic activity of enzymes. It also resembled the findings reported for prior studies [ 46 , 47 ].
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…The mutations in the course of evolution of Bs DyP were inserted in flexible loops and in a small helix close to the heme pocket ( Figure 3 a,b). Flexible loops in the proximity of active sites frequently play roles in catalysis as they interact with solvent and substrates [ 53 , 54 ]; it is widely accepted that their pronounced conformational flexibility may contribute to their function, in substrate selectivity and recognition, and the facilitation of substrate binding, as well as protein evolution, as they represent molecular elements of variability [ 55 ]. Loop 1 (222–250) and loop 3 (334–342) are predominantly located at the distal side of the heme and comprise the catalytic residues D240 and R339, respectively.…”
Section: Resultsmentioning
confidence: 99%
“… 1 In particular, the importance of flexibility of loops for protein function and enzyme catalysis has gained increased attention. 15 For some enzymes such as terpene cyclases, 16 loop dynamics is a necessity for expedient catalysis by capping the active site following substrate binding, shielding reactive intermediates from the solvent, and enabling efficient transition-state stabilization. 16 Proteins with flexible loops have previously been shown to exhibit allokairic regulation.…”
Section: Introductionmentioning
confidence: 99%